Design and Evaluation of a Web-Based E-Commerce System for Optimizing MSME Business Processes - Nuswantoro, Setio Ardy; Windiarti, Ika Safitri; Ulfi, Muhammad; Suwandini, Najwa Aulia (Insect (Informatics and Security): Jurnal Teknik Informatika, 2026)
This research focuses on designing and evaluating a web-based e-commerce system intended to improve the business processes of Noor Laila UMKM in Palangka Raya City, Central Kalimantan. The development process applied the Waterfall methodology, consisting of stages such as requirements analysis, system design, implementation, and testing. Data were gathered through direct observation, interviews with the owner and two employees, along with documentation of transactions and financial records. The system was launched online via https://luwukcraft.com, allowing broader customer access. Regarding system evaluation, black-box testing confirmed that all 35 functional scenarios operated successfully with a 100% pass rate. The User Acceptance Test with 89 respondents produced an average rating of 4.5 out of 5, reflecting strong usability and alignment with user needs. Performance testing under 89 concurrent users recorded an average response time of 2.3 seconds, a 98% transaction success rate, and 99.2% system availability during the two-month trial. From a business standpoint, the system contributed significantly to operational improvements, including a 68% increase in order processing efficiency, an 83% reduction in data entry errors, a 92% faster financial reporting process, a 146% rise in weekly transactions, and a 40% increase in average sales. Overall, these results indicate that the implemented web-based e-commerce system effectively facilitates UMKM digital transformation, enhances workflow efficiency, and strengthens business competitiveness.